Improving Understanding of The Break of Triangle Concepts Through The Application of Bruner's Theory In Class IV Students of SDN 7 Kontunaga Kabupaten Muna - WA ODE DARNIA Darni; Sundari Hamid (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Bruner's learning theory is a teaching model developed based on a cognitive view of learning and constructivation where the contents of Bruner's theory is a student-centered learning approach with (1) an active stage; learning using concrete objects or real situations, (1) the iconic stage; presented in the form of visual images or images and (3) symbolic stages; write symbols related to symmetry of flat shapes, which are organized in such a way as to make students play an active role in learning. Students learn through active involvement with concepts and principles, and the teacher encourages students to gain experience by carrying out activities that enable them to discover concepts and principles for themselves. The purpose of this research is to improve understanding of the concept of the area of a triangle in class IV students at SDN 7 Kontunaga Kab. Muna through the Application of Bruner's Theory. The method used in this study was classroom action research by adapting the research design of Kemmis and Mc. Taggart. The research was conducted in two cycles. Each cycle consists of four stages of activity namely, planning, action, observation, and reflectionthe source of the data in this study were research personnel consisting of students and teachers The collection of data in this study is quantitative data and qualitative data consisting of learning achievement tests, observation results and interview results. Based on research data with the application of Bruner's theory, satisfactory results were obtained, namely in the pre-action 12 students (66.66%) received a low score, 6 students (33.33%) received an adequate score, and no student (0 %) who got good grades. In cycle I, out of 18 students who took the formative test, students who scored above 7.0 were 11.11% (2 people) with an average score of 4.72. In cycle II this increased, namely all students had obtained the lowest score of 7.0 with an average value of 7.5 were 100%. it is concluded that learning the Application of Bruner's Theory can improve understanding of the concept of the area of a triangle in class IV students.